Biomechanical analysis a sequence of angular velocity and coordinated muscles activity during baseball hitting - Lim, Y.-T.; Park, J.-S.; Kwon, M.-S. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this study was to analyse a sequence of rotations and coordinated muscles activities of upper body. Using kinematic and EMG data from 3 recreational university baseball players participating in this study, we computed the angular velocity of trunk, pelvis, bat and trunk-pelvis rotation angle and PMT of upper body muscles. Trunkpelvis rotation angle was 22 ° before the bat-ball contact. The pelvis, trunk, and bat showed a sequence of angular velocity beginning with the hip, followed by the trunk, and end tip of the bat. Additionally, PMT of upper body muscles generated right pectoralis major(1.03 sec.), right external oblique(1.11 sec.), left thoracloumbar fasci(1.12 sec.), left external oblique(1.13 sec.), right latissimus dorsi(1.15 sec.), left latissimus dorsi(1.16 sec.), right thoracloumbar fascia(1.16 sec.), left pectoralis major(1.25 sec.), on at a time during baseball hitting motion. PMT of upper body muscles were related to the shifting and rotating of body segment and this action can be considered the coordinated muscle activities of upper body.